Business Development Strategy on Traditional Coconut Oil (Lengis Tanusan) Production during the Covid-19 Outbreak - Guntari, Ni Kadek Sri; Putu Oka Suardi, I Dewa; Parining, Nyoman (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 2 (2021): Vol.15, No.2, 2021DO - 10.24843/SOCA.2021.v15.i02.p11, 2021)
Covid-19 outbreak leads to various issues in the traditional coconut oil business. A low-level purchasing power, low-level production of the oil, and poor marketing skill contribute to hindrances in running the business. This study aimed to investigate the business development strategy of traditional coconut oil during the Covid-19 outbreak in Sulang Village. Eight key informants participated in this study. Data was collected through the in-depth interview, documentation, and observation and analyzed through the SWOT dan QSPM analysis. Results revealed that the internal factors that play as the strength factor in this business were the unique savory taste of the traditional coconut oil, while the weakness factor was the low production of the oil during the Covid-19 outbreak. The external factor identified as the opportunity in this business was its close location to Paksebali and Pasek Gunaksa market. The threat factor found was the healthy lifestyle that tended to recommend a low fatty food diet. According to the alternative strategy analysis, there were 11 strategies found in developing and maintaining the traditional coconut oil business in Sulang Village. Consignments with merchants around Tukad Yeh Unda was selected as the priority strategy to maintain and improve this business. Strategies listed in this study expected to be a recommendation for the traditional coconut oil owners to manage their business during the Covid-19 outbreak.